Kesaksian dalam Konteks Undang-undang Keterangan Mahkamah Syariah di Malaysia: Analisis dari Perspektif Mazhab Syafi'i - Md. Noor, Ruzman (Jurnal Fiqh, 2008)
Law of Evidence has been enacted to provide the court with the rules and regulations pertaining to the determination of relevant facts and how they are proved during trial. One of the main method of proving is testimony by witnesses. In fact, this is the crucial part of the law which distinguish between the concept of witnesses applicable in Shariah Court and the one that applied in Civil Court. The objective of this article is to identify the influence of the Madhhab Shafi'i in this respective method of proving by analyzing some provisions of the law. The law of evidence in Shariah Court has differentiates between the method of bayyinah and shahadah. The opinions from Madhhab Shafi'i have dominated most of the provisions. However they are not strictly adhere to this particular mazhab and by employing the mechanism of al-talfiq, opinions from other scholars are also taken into consideration particularly on the issue of al-bayyinah and al-syahadah.